The NLRP3-Caspase 1 Inflammasome Negatively Regulates Autophagy via TLR4-TRIF in Prion Peptide-Infected Microglia - Lai, Mengyu; Yao, Hao; Shah, Syed Zahid Ali; Wu, Wei; Wang, Di; Zhao, Ying; Wang, Lu; Zhou, Xiangmei; Zhao, Deming; Yang, Lifeng (Frontiers in Aging Neuroscience, 2018)
Prion diseases are neurodegenerative disorders characterized by the accumulation of misfolded prion protein, spongiform changes in the brain, and brain inflammation as a result of the wide-spread activation of microglia. Autophagy is a highly conserved catabolic process for the clearance of cytoplasmic components, including protein aggregates and damaged organelles; this process also eliminates pathological PrPSc as it accumulates during prion infection. The NALP3 inflammasome is a multiprotein complex that is a component of the innate immune system and is responsible for the release of pro-inflammatory cytokines. Our previous study showed that the neurotoxic prion peptide PrP106-126 induces NALP3 inflammasome activation and subsequent IL-1β release in microglia. Autophagy is involved in the regulation of the immune responses and inflammation in many diseases including neurodegenerative diseases. However, the relationship between autophagy and NALP3 inflammasome in prion diseases has not been investigated. In this study, we demonstrated that the processing and release of mature IL-1β is significantly enhanced by the inhibition of autophagy. Conversely, gene-silencing of the NALP3 inflammasome promotes autophagy. Suppression of TRIF or TLR4 by siRNA attenuated PrP106-126-induced autophagy, which is indicating that the TLR4-TRIF signaling pathway is involved in PrP106-26-induced autophagy. Caspase 1 directly cleaved TRIF to diminish TLR-4-TRIF mediated autophagy, Our findings suggest that the inhibition of autophagy by NALP3 inflammasome is probably mediated by activated Caspase-1-induced TRIF cleavage. This is the first study reporting that the NALP3 inflammasome complex negatively regulates autophagy in response to PrP106-126 stimulation in microglia, and partly explain the mechanism of autophagy inhibition by Caspase-1 in PrP106-126-induced BV2 cell activation. Our findings suggest that autophagy up-regulation and inhibition of Caspase-1 may protect against prion-induced neuroinflammation and accelerate misfolded protein degradation and are potential therapeutic approaches for prion diseases.